2009
DOI: 10.3329/uhj.v4i2.2073
|View full text |Cite
|
Sign up to set email alerts
|

Study on serum Lipoprotein (a) level in preeclamptic Bangladeshi women

Abstract: It is a case control study which was design to know the association of serum Lipoprotein (a) level in preeclamptic (PE) in women. This study was carried out in department of Obstetrics and Gynecology, Sir Salimullah Medical College Hospital, Mitford, Dhaka. Total number of subjects was 100. Out of which 50 were cases and 50 were controls. Cases were physically and clinically proved PE patients. Controls were age, parity and gestational age matched. Three ml of blood were collected from each subjects, serum fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…An almost similar result was observed in Ferdous et al's study. 17 The present study demonstrated that the mean serum homocysteine level was significantly higher in preeclampsia than that in the control group and that the mean serum homocysteine of preeclamptic women progressively increases with the severity of preeclampsia with the highest level of serum homocysteine being observed in eclamptic women. These results are fortified by the findings of other studies as well.…”
Section: Discussionsupporting
confidence: 48%
“…An almost similar result was observed in Ferdous et al's study. 17 The present study demonstrated that the mean serum homocysteine level was significantly higher in preeclampsia than that in the control group and that the mean serum homocysteine of preeclamptic women progressively increases with the severity of preeclampsia with the highest level of serum homocysteine being observed in eclamptic women. These results are fortified by the findings of other studies as well.…”
Section: Discussionsupporting
confidence: 48%